Guaranteed Wages and Social Security for Daily Workers at PTP Nusantara XIV Awaya - Arter Lukas Tulia (JUSTISI, 2025)
The study aims to discuss the protection and fulfillment of the rights of casual workers at PTP Nusantara XIV Awaya. This study focuses on the regulation and implementation of wage guarantees and social security programs for casual workers at PTP Nusantara XIV Awaya. The research method applied in this study is normative legal analysis, which includes an analysis of secondary data and the use of interviews with respondents or informants as primary data. The novelty of this research lies in its focus on the rights of daily workers at PTP Nusantara XIV Awaya, which are not explicitly regulated in employment agreements. This irregularity creates legal uncertainty that directly impacts the company's fulfillment of workers' rights. The results of the study show that casual daily workers at PTP Nusantara XIV Awaya do not receive adequate legal protection and certainty regarding their rights to wages and social security. These findings are based on interviews with respondents and an analysis of the applicable piecework employment agreements. The employment contract does not clearly stipulate the amount of wages, potentially leading to legal uncertainty in the implementation of workers' rights. Additionally, the company is obligated to fulfill workers' social security rights in accordance with applicable laws and regulations. However, in practice, PTP Nusantara XIV Awaya fails to fulfill this obligation for daily casual workers. The study concluded that daily workers at PTP Nusantara XIV Awaya, based on interviews with one of the daily workers, a foreman, and members of the company's legal team, do not receive social security programs such as BPJS Ketenagakerjaan. In addition, wage rates are not specifically regulated in the work agreement. However, these workers' rights are regulated and mandated by Government Regulation No. 35 of 2021 on social security and labor.